The Roles of Factors in Communication Styles Influencing the Marriage of Bataknese and the Javanese - Alice Gunasirini (Institute of Research and Community Outreach - Petra Christian University, 2018)
This discussion here is about the different styles of communication in the marriage of the Bataknese and the Javanese. The research is how the Bataknese as the nomads interact in communication in their mix-marriage. To analyze the phenomenon, I will use the theories of communication and acculturation and the method of qualitative. By using the theories and method I will analyze how the Bataknese and the Javanese overcome their conflicts in their marriage due to the differences in communication to reach the harmony in their mix-marriage.